Strain-Reduced Micro-LEDs Grown Directly Using Partitioned Growth - Lu, Shunpeng; Zhang, Yiping; Zhang, Zi-Hui; Tsai, Ping Chieh; Zhang, Xueliang; Tan, Swee Tiam; Demir, Hilmi Volkan (Frontiers in Chemistry, 2021)
Strain-reduced micro-LEDs in 50 μm × 50 μm, 100 μm × 100 μm, 200 μm × 200 μm, 500 μm × 500 μm, and 1,000 μm × 1,000 μm sizes were grown on a patterned c-plane sapphire substrate using partitioned growth with the metal-organic chemical-vapor deposition (MOCVD) technique. The size effect on the optical properties and the indium concentration for the quantum wells were studied experimentally. Here, we revealed that the optical properties can be improved by decreasing the chip size (from 1,000 to 100 µm), which can correspondingly reduce the in-plane compressive stress. However, when the chip size is further reduced to 50 μm × 50 μm, the benefit of strain release is overridden by additional defects induced by the higher indium incorporation in the quantum wells and the efficiency of the device decreases. The underlying mechanisms of the changing output power are uncovered based on different methods of characterization. This work shows the rules of thumb to achieve optimal power performance for strain-reduced micro-LEDs through the proposed partitioned growth process.